Bioenergetic constraints on the origin of autotrophic metabolism - Boyd, Eric S. (Philos Trans A Math Phys Eng Sci, 2020)
Autotrophs form the base of all complex food webs and seemingly have done so since early in Earth history. Phylogenetic evidence suggests that early autotrophs were anaerobic, used CO(2) as both an oxidant and carbon source, were dependent on H(2) as an electron donor, and used iron-sulfur proteins (termed ferredoxins) as a primary electron carrier. However, the reduction potential of H(2) is not typically low enough to efficiently reduce ferredoxin. Instead, in modern strictly anaerobic and H(2)-dependent autotrophs, ferredoxin reduction is accomplished using one of several recently evolved enzymatic mechanisms, including electron bifurcating and coupled ion translocating mechanisms. These observations raise the intriguing question of why anaerobic autotrophs adopted ferredoxins as central electron carriers only to have to evolve complex machinery to reduce them. Here, we report calculated reduction potentials for H(2) as a function of observed environmental H(2) concentration, pH and temperature. Results suggest that a combination of alkaline pH and high H(2) concentration yield H(2) reduction potentials low enough to efficiently reduce ferredoxins. Hyperalkaline, H(2) rich environments have existed in discrete locations throughout Earth history where ultramafic minerals are undergoing hydration through the process of serpentinization. These results suggest that serpentinizing systems, which would have been common on early Earth, naturally produced conditions conducive to the emergence of H(2)-dependent autotrophic life. The primitive process of hydrogenotrophic methanogenesis is used to examine potential changes in methanogenesis and Fd reduction pathways as these organisms diversified away from serpentinizing environments. This article is part of a discussion meeting issue ‘Serpentinite in the earth system’.